Sungai Isap secondary school management website - Amirah, Mohd (2012)
Internet has become good medium that employs networks to allow people to introduce their organization to world. Proper information management can be expressed into official website of that organization.This project is conducted because Sungai Isap Secondary School does not have proper information management to view itself to the public.Proper information management is necessary to providing the public with useful information.This project investigatesthe efficiency of information management via website and analyses the usefulness of the website as the medium to manage information.The scope of this research is Sungai Isap Secondary School.The target users in this system are public, students,teachers,school administers and government (Ministry of Education).The data are collected based on structured interview to users to identity their requirements of the proposed system.The questions focused on three aspects of the proposed website.These aspects are the website design,the content,functionality and usability.The advantage of the proposed system,to society is that the public can view proper information via the school website.